Dongeng Aceh: Pangeran Amat Mude dalam Animasi 2 Dimensi (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2021)
Nanggroe Aceh Darussalam is one of the provinces in Indonesia, which has a rich cultural heritage. One of them is folk tales. After conducting the research, In these days the story of Aceh has slowly not recognized even by the people of Aceh itself. If we continue to ignore this case, Aceh's tale might be forgotten slowly. Regarding to that case, this 2D Animation work created by purposed to perpetuate and to increase the number of awareness current generation of our local fables. Also, the media that used in this work was based on current trends. This work visualised by 2D Animation video with the title of work called "Pangeran Amat Mude" also this work was made in 5 chapters. The tale of "Pangeran Amat Mude" is a parable tale that contains values moral values and education in it so that this work can be displayed as a media entertainment and education. "Pangeran Amat Mude" is displayed with MP4 extension specifications, 1920 x 1080 video resolution and frame rate of 29.7 frames per second. The research method used is qualitative research. Some main element of this research is interviews with group of people, observations and conducting field studies of the work similar work. The survey was conducted on a small group of Acehnese people and school children Basic with ages 7-12 years as a fundamental thing in designing this folk tales animation work.Overall. "Pangeran Amat Mude" was visualised in different way compared to existing similar work that already on internet. The story used is a new ones that have been adopted from traditional stories. Therefore, this folk tales work become more interesting with the moral and educational values contained in the story